(3QSGdI aj GdfaSs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdeaGQbGJ CQHY eQGJH eNJdaI GdMbGjb GdeQJHI GdChdi GdehLhO GdPi dG SHH dg s
(3BNQgG (B:s
(3dcGfJ GdfaS TF hGMO YGdeI hLGedI eYkG s
(3Vef eLehY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B896s
Keywords: (3GdadSaI hGdefWbs